Inventory of Medicinal Plants Around Kereng Bangkirai Tourism Village, Central Kalimantan: Inventarisasi Tumbuhan Obat di Sekitar Desa Wisata Kereng Bangkirai, Kalimantan Tengah - Raudhah (Harati : Journal of Science Education, 2025)
Kereng Bangkirai Village is one of the tourist villages in the city of Palangka Raya, Central Kalimantan, Indonesia. This study aims to inventory medicinal plants in the Kereng Bangkirai tourist village. The method used in this study is field exploration research with data collection techniques in the form of observation and interviews, then data analysis techniques in the form of qualitative descriptive. The results of the study showed that there were 10 species of plants that were utilized by the community in the Kereng Bangkirai village area as medicinal plants. Where the utilization is from the roots, stems and leaves. This finding is certainly a finding that will be very useful for the development of the potential of local plants in an area, especially in Central Kalimantan